Would the skyrocketed advances of immune checkpoint inhibitors over chemotherapy be stumbled by the safety issues? - Shohdy, Kyrillus S.; Abdel-Rahman, Omar (Translational Cancer Research; Vol 6, Supplement 6 (August 29, 2017): Translational Cancer Research, 2017)
Immune checkpoint inhibitors (ICIs) have inaugurated a new era in the treatment of advanced malignancies. It is not only associated with higher progression-free survival and overall-survival but also a durable response that reached to 10 years in certain subsets of patients (1). This superiority over conventional chemotherapy regimens guaranteed an approval for ICIs in second and even first lines in treatment of non-small cell lung cancer (NSCLC), melanoma and renal cell carcinoma. Of those molecularly defined immune targeting, PD-1 and PD-L1 pathways are influential in suppressing effector immune response against tumor. That’s why anti-PD-1 and PD-L1 monoclonal antibodies (mAbs) could induce sustainable anti-tumor immune response. Unfortunately, this immune system manipulation may lead to emergence of autoimmune manifestations, usually reported as immune-related adverse effects.